Quality of work life and its impact on job performance among nurses at Hospital Umum Sarawak / Nur Shafinaz Mohamad Zaini - Mohamad Zaini, Nur Shafinaz (2019)
Poor quality of nursing care delivery is one of the challenges in the nursing profession. Nowadays nursing working environment is very hectic due to challenging work condition, shortage of nurses, low salary, work place restrictions as well as shift work. There is a need to study the quality of work life nurses and how it affects the job performance as nurses. This study examines quality of life and its impact on job performances among 320 nurses at Hospital Umum Sarawak. The instrument used to measure quality of work life is adapted by Brooks and Walter. The instrument consists of 4 dimensions work life/home life, work design, work context and work environment. Job performance is measure using an instrument developed by Boman & Mothowidlo (1993). Job performance consists of two dimension that are task and contextual performance. This study will use a questionnaire to collect the data will be analyse using descriptive and inferential descriptive. This study will provide inside on the relationship between quality of work life and job performance among nurses in the government hospital. The finding of this study may have the Ministry of Health to improve the quality of work life on job performance in the government hospitals in Malaysia.